Comparison of torch with electric arc casting in the lost wax technique for the cast dental stud protocol - Víctor Hugo Gonzalo Quispe Mamani; César Alberto Luna Castillo; Dina Miryan Alanoca Sejje; Luis Alexander Orrego-Ferreyros (PLoS ONE, 2025)
The aim of this study was to compare the compressive strength, microstructural characteristics, and cost-effectiveness of cast dental posts fabricated using two techniques: torch casting (TC) and electric arc casting (EAC), both integral to the lost wax method. Employing an applied research approach with an experimental design, the study analyzed 40 non-precious gold (NPG) alloy cast posts, divided equally into two groups of 20 for each technique. The selection process was non-probabilistic and based on convenience, with specific inclusion and exclusion criteria to ensure precision and relevance. The results reveal a significant advantage for the EAC technique. In Essay 1, EAC posts exhibited a mean compressive strength of 206.102 MPa, compared to 157.207 MPa for TC posts. Similarly, in Essay 2, EAC posts showed a mean strength of 172.625 MPa versus 136.303 MPa for TC posts. These differences were statistically significant (p < 0.05), with EAC posts also displaying smaller failure diameters and areas, suggesting better load distribution. Morphological and microstructural analysis using scanning electron microscopy (SEM) revealed a porous surface with irregular topography in both techniques. However, EAC samples displayed crystalline growths within the copper matrix, indicating a non-homogeneous stoichiometry, while TC samples showed aluminum-enriched zones, suggesting a non-uniform elemental distribution. Chemical composition analysis via energy-dispersive spectroscopy (EDS) identified copper (Cu) as the predominant element in both samples, with trace elements such as aluminum (Al), nickel (Ni), and iron (Fe) also present. X-ray diffraction (XRD) analysis further revealed distinct crystalline phases, with EAC samples exhibiting a higher proportion of Cu₃Zn and gamma-Fe phases compared to TC samples. A cost analysis using Python 3.13 and Monte Carlo simulation with 1,000 iterations revealed that EAC is more expensive, with a total cost per unit of 2.181compared to 1.467 for TC, primarily due to higher operational costs. The Mann-Whitney U test confirmed significant differences in cost distributions (p < 0.001), indicating that EAC has higher and more variable costs. In conclusion, the study demonstrates that EAC produces dental models with significantly higher compressive strength and a more refined microstructure compared to TC, enhancing restoration durability. However, its higher operational costs must be considered. These findings provide valuable information for dental professionals, particularly in low- to middle-income countries, and suggest that future research should explore additional properties such as corrosion resistance and biocompatibility to further validate the clinical applicability of these materials.